Prise en charge anesthésiologique des abdomens aigus chirurgicaux chez l’adulte au département d’anesthésie réanimation et de médecine d’urgence du CHU Gabriel Toure. - ALMEIMOUNE, Abdoulhamidou; Madane Thierno, Diop; Moustapha, MANGANE; Seidou Alaji, DÉMBELE; Mahamadoun, COULIBALY; Youssouf, SOGOBA; Chiad mahamadoun CISSE, Abdoulaye; KOITA, Siriman; SANGARE, Harouna; Yattara, Sidy; KOITA, Siriman; TRAORE, Aliou; et al. (International Journal of Scientific Research and Management (IJSRM), 2021)
The anesthesiological management of acute surgical abdomens remains a delicate exercise for anesthesiologists and resuscitators, given the major volume disturbances, the delay in diagnosis with its corollary of septic shock, and the dysfunction of the emergency departments with which they are confronted. The objectives of this work were to study clinical and anesthesiological aspects, as well as intraoperative morbidity and mortality related to acute surgical abdomens. We conducted a prospective 12-month study. In this study was included Any patient received in the emergency room of the C.H.U Gabriel Touré in whom the diagnosis of acute surgical abdomen had been retained on the basis of clinical and paraclinical signs who agreed to participate. Results: During our study period, acute surgical abdomens represented 631/1335 cases of all emergency surgeries. Fifty-six of them were referred to intensive care immediately after surgery. Peritonitis represented 376 cases (61%) followed by intestinal obstruction (135/631), appendicitis (76/631) and hemoperitoins (33/631). The clinical presentation on admission was dominated by signs of hypovolemic and infectious delay. The average hemoglobin level was 12.03g / dl. Renal impairment (clearance